Neisseria meningitidis accumulate in large organs during meningococcal sepsis - Brusletto, Berit Sletbakk; Hellerud, Bernt Christian; Øvstebø, Reidun; Brandtzaeg, Petter (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Neisseria meningitidis (Nm) is the cause of epidemic meningitis and fulminant meningococcal septicemia. The clinical presentations and outcome of meningococcal septic shock is closely related to the circulating levels of lipopolysaccharides (LPS) and of Neisseria meningitidis DNA (Nm DNA). We have previously explored the distribution of Nm DNA in tissues from large organs of patients dying of meningococcal septic shock and in a porcine meningococcal septic shock model. Objective: 1) To explore the feasibility of measuring LPS levels in tissues from the large organs in patients with meningococcal septic shock and in a porcine meningococcal septic shock model. 2) To evaluate the extent of contamination of non-specific LPS during the preparation of tissue samples. Patients and methods: Plasma, serum, and fresh frozen (FF) tissue samples from the large organs of three patients with lethal meningococcal septic shock and two patients with lethal pneumococcal disease. Samples from a porcine meningococcal septic shock model were included. Frozen tissue samples were thawed, homogenized, and prepared for quantification of LPS by Pyrochrome® Limulus Amoebocyte Lysate (LAL) assay. Results: N. meningitidis DNA and LPS was detected in FF tissue samples from large organs in all patients with meningococcal septic shock. The lungs are the organs with the highest LPS and Nm DNA concentration followed by the heart in two of the three meningococcal shock patients. Nm DNA was not detected in any plasma or tissue sample from patients with lethal pneumococcal infection. LPS was detected at a low level in all FF tissues from the two patients with lethal pneumococcal disease. The experimental porcine meningococcal septic shock model indicates that also in porcinis the highest LPS and Nm DNA concentration are detected in lungs tissue samples. The quantification analysis showed that the highest concentration of both Nm DNA and LPS are in the organs and not in the circulation of patients with lethal meningococcal septic shock. This was also shown in the experimental porcine meningococcal septic shock model. Conclusion: Our results suggest that LPS can be quantified in mammalian tissues by using the LAL assay.